Comparison of the PCR-RFLP and ITS-rDNA sequencing technique for phylogenetic analyze of Colletotrichum spp. isolates - Ribeiro, Diorvania Cardoso; Bogo, Amauri; Dantas, Adriana Cibele de Mesquita; Gomes, Eliane Aparecida; Coelho, Cileide Maria Medeiros; Guidolin, Altamir Frederico (Revista de Ciências Agroveterinárias, 2009)
The genus Colletotrichum is one of the most important pathogenic fungi group, mainly in tropical and subtropical areas of the world. The identification of Colletotrichum species is difficult due to their large morphological variation. Molecular methods, such as PCR-RFLP and rDNA sequence, have been very useful for phylogenic studies of this pathogen. The objective of this work was to compare the PCRRFLP and rDNA sequence techniques for phylogenetic analysis of Colletotrichum spp. Isolates. All isolates were cultivated from cultures grown on Potato Sucrose Broth (PSB), for one week at 24oC. The amplification of the rDNA was accomplished by the ITS1 and ITS4 initiators, followed by digestion of the ITS area using restriction enzymes (Rsa I, Alu I, Hinf I, Hpa II, Hha I, Xho I, Acc I, Eco RI and Taq I). The revelation was made in agarose gel 2%. The primers produced fragments from 600 to 90 pb. The amplified fragment was purified with the kit QIAquick Gel Extraction Kit 250 (Unisciense of Brazil) and the internal transcribed spacer region of the rDNA (ITS1-ITS2) was sequenced. The ITS1- 5.8S-ITS2 sequences were aligned with the software ClustalW and the phylogenetic tree was constructed using the software Mega 3.1. The products obtained with the amplification of the ITS-rDNA produced a fragment of approximately 600 pb, for all the isolated analyzed. The PCR-RFLP technique is not very efficient to separate Colletotrichum spp because some of the restriction enzymes acted in conserved regions of the rDNA, affecting the results. However, the sequencing technique was accurate to separate Colletotrichum isolates per species and hosts, allowing the inclusion of published GenBank sequences. The PCR-RFLP technique should be used together with the rDNA sequencing technique in order to get cheaper and more reliable results in the phylogenic studies of microorganisms.